Contestation of Javanese Culture and Identity in Deli: An Analysis of Jawa Deli Wedding Ceremonies Using the Bergerian Approach - Khairani, Leylia (Universitas Negeri Medan, 2024)
This paper aims to demonstrate that Javanese culture is not uniform. According to several research findings, there are numerous cultural variances among Javanese people, who regard themselves as different from other Javanese. In the Deli Serdang Regency, the marriage ceremony analyzed in this study does not only see a rich parade of a Javanese Deli cultural tradition. On the other hand, the Javanese Deli's marriage ceremony procession in Deli Serdang depicts identity that is produced through a historical process tailored to their socio-cultural environment. In this study, the building of the Javanese Deli identity during the wedding ceremony is examined from a Bergerian perspective, in which the Javanese Deli identity is constantly transformed and shaped socially and culturally. When in Deli, the essence of Java Deli is significantly influenced by changing situations and conditions that continue to evolve. As a result of the externalization, objectification, and internalization processes, Java Deli's manufactured identity is situational.